Computed Tomography Identifies Patients at High Risk for Stroke After Transient Ischemic Attack/Nondisabling Stroke: Prospective, Multicenter Cohort Study. Issue 1 (January 2015) - Wasserman, Jason K.; Perry, Jeffrey J.; Sivilotti, Marco L.A.; Sutherland, Jane; Worster, Andrew; Émond, Marcel; Jin, Albert Y.; Oczkowski, Wieslaw J.; Sahlas, Demetrios J.; Murray, Heather; MacKey, Ariane; Verreault, Steve; et al.
Abstract : Background and Purpose—: Ischemia on computed tomography (CT) is associated with subsequent stroke after transient ischemic attack. This study assessed CT findings of acute ischemia, chronic ischemia, or microangiopathy for predicting subsequent stroke after transient ischemic attack. Methods—: This prospective cohort study enrolled patients with transient ischemic attack or nondisabling stroke that had CT scanning within 24 hours. Primary outcome was subsequent stroke within 90 days. Secondary outcomes were stroke at ⩽2 or >2 days. CT findings were classified as ischemia present or absent and acute or chronic or microangiopathy. Analysis used Fisher exact test and multivariate logistic regression. Results—: A total of 2028 patients were included; 814 had ischemic changes on CT. Subsequent stroke rate was 3.4% at 90 days and 1.5% at ⩽2 days. Stroke risk was greater if baseline CT showed acute ischemia alone (10.6%; P =0.002), acute+chronic ischemia (17.4%; P =0.007), acute ischemia+microangiopathy (17.6%; P =0.019), or acute+chronic ischemia+microangiopathy (25.0%; P =0.029). Logistic regression found acute ischemia alone (odds ratio [OR], 2.61; 95% confidence interval [CI[, 1.22–5.57), acute+chronic ischemia (OR, 5.35; 95% CI, 1.71–16.70), acute ischemia+microangiopathy (OR, 4.90; 95% CI, 1.33–18.07), or acute+chronic ischemia+microangiopathy (OR, 8.04; 95% CI, 1.52–42.63) was associated with a greater risk at 90 days, whereas acute+chronic ischemia (OR, 10.78; 95% CI, 2.93–36.68), acute ischemia+microangiopathy (OR, 8.90; 95% CI, 1.90–41.60), and acute+chronic ischemia+microangiopathy (OR, 23.66; 95% CI, 4.34–129.03) had greater risk at ⩽2 days. Only acute ischemia (OR, 2.70; 95% CI, 1.01–7.18; P =0.047) was associated with a greater risk at >2 days. Conclusions—: In patients with transient ischemic attack/nondisabling stroke, CT evidence of acute ischemia alone or acute ischemia with chronic ischemia or microangiopathy was associated with increased subsequent stroke risk within 90 days.